Diagnosis and Treatment of Advanced ALK Rearrangement-Positive Non-Small-Cell Lung Cancer in Portugal: Results of a National Questionnaire - Ana Figueiredo; Ana Rodrigues; Carina Gaspar; Margarida Felizardo (Adis, Springer Healthcare, 2023)
Abstract Background Rearrangements in the anaplastic lymphoma kinase (ALK) gene define a molecular subgroup of non-small-cell lung carcinoma (NSCLC) that should be treated with ALK-targeting tyrosine kinase inhibitors (TKIs). Objective This study aimed to portray the Portuguese reality about the diagnosis and treatment of stage IV ALK-positive NSCLC. Methods Institutions that treat lung cancer in Portugal were invited to participate in an anonymous electronic questionnaire. A total of 22/35 geographically dispersed institutions responded. A descriptive statistical analysis of the results was performed. Results Reflex molecular testing was done in 54.6% of the institutions. Next-generation sequencing (NGS) was the preferred diagnostic method (90.9%). Typically, physicians obtained molecular study results within 14-21 days. Alectinib was the most commonly used first-line treatment. For patients with brain metastases, 86.4% of the physicians preferred alectinib and 13.6% preferred first-line brigatinib. In the case of asymptomatic oligoprogression in the central nervous system, 85.7% of physicians performed local treatment and kept the patient on a TKI; if symptomatic, 66.7% gave local treatment and stayed with the TKI, while 28.6% gave local treatment and altered the TKI. For patients with symptomatic systemic progression, 47.6% and 38.1% of physicians prescribed lorlatinib after initial treatment with alectinib or brigatinib, respectively. After progression on lorlatinib, 42.9% of respondents chose chemotherapy and 57.1% requested detection of resistance mutations. Conclusions NGS is widely used for the molecular characterization of ALK-positive NSCLC in Portugal. The country has access to up-to-date therapy. Overall, national clinical practice follows international recommendations for the diagnosis and treatment of ALK-positive NSCLC.